Folk Tales and Fables from The Gambia. - Bojang, Sukai Mbye (Educational Services, 2013)
The stories were gathered from the Serahulay, Wollof, Mandingo and Fula people of Gambia. The the themes in the nine stories contained in this Volume surround arranged marriages, polygamy and the lives of young girls in general.